ESTIMATION OF GENETIC PARAMETERS AND BREEDING VALUE OF SEXUAL AND EGG PRODUCTION TRAITS IN IRAQI LOCAL CHICKENS - A. J. SH. Al-Ghabban; Waleed M. Razuki; E. H. Al-Anbari (The Iraqi Journal of Agricultural science)
This study was conducted to estimate (Co) variance components of a sexual and egg production traits in Iraqi brown local chickens. Data on 2234 pedigreed hens for successive six generations of selection for high egg production during the first 24 weeks of laying were used. Data of first egg weight (FEWT), body weight at sexual maturity (BWSM), age at sexual maturity (ASM), egg number (EN), egg weight (EW) and egg mass (EM) were recorded individually. The univariate and bivariate animal models under Average Information Restricted Maximum Likelihood (AI-REML) were applied to estimate the variance component and the BLUP breeding values. The average of the traits mentioned above was 35.7g, 1489.59g, 149.31d, 109.32 egg/hen, 44.80g and 4887.72g respectively. Heritability estimates based on individual animal model was 0.17, 0.42, 0.39, 0.40, 0.68 and 0.40 for the traits mentioned above respectively. The genetic and phenotypic correlations between sexual traits (ASM, BWSM, and FEWT) showed moderate and positive values.  Genetic correlation between sexual traits (ASM, BWSM, and FEWT) with EN and EM was negative. Genetic correlations between (EN and EW), (EN and EM) and (EW and EM) were -0.105,0.902 and 0.337 respectively. Genetic correlations between ASM with EW were negative while BWSM and FEWT with EW were Positive. Average breeding values across generation tend to be positive in productive traits but it was negative in sexual traits. In conclusion, a good performance and reliable estimation of genetic parameters and BLUP breeding value shown in the current study could be revealed that Iraqi brown local chickens have a good genetic potential for egg production traits and respond well to selection for increasing egg production traits.